The Effects of Static Magnetic Field and Short Wave Ultraviolet on Some Pathogenic Fungi - Ahmad, Dhahir Tahir; Al-Barzenji, Vian Badraddin; Abdulkareem, Nashwan karkhi (Diyala Journal of Medicine, 2019)
Background: Electromagnetic radiation is the radiant energy released by certain electromagnetic processes. Visible light is one type of electromagnetic radiation; other familiar forms are invisible electromagnetic radiations such as radio waves, infrared light and X rays. Objective: To estimate the effects of static magnetic field and short wave ultraviolet on different types of pathogenic fungi (growth of fungi, diameter and pigmentation of colony). Material and method: This study was carried out at biophysics and microbiology research lab, College of Medicine-Erbil, during the period from January 2010 till April 2010, seven types of fungi were included, growing culture was examined carefully and colony morphology was recorded, then preparation of slides from the colony was stained by Lacto phenol or Gram stain. Examination were made on the fungi (Fusarium solani.,Penicillium sclerotogenum, Candida albicans, Aspergillus parasiticus, Ulocladium spp., Penicillium citrinum, Aspergillus tamari), they were isolated from the dusts, cultures were grown on Sabourauds dextrose agar. The inoculums for our experiments were taken from the growing zone of basic cultures. All of these fungi are exposed to (375-750) gausses of static magnetic field and short long wave ultraviolet at a periodic time (2,4,6,8,10,12,14,16,18,20,22,24.26) hours each days respectively. Results: The results of this study show that by using t-test there was significance difference between experimental and control groups of fungi length after exposures to the mentioned field at periodic times (2,4,6,8,10,12,14,16,18,20,22,24,26) day's respectively, shows that there is significance difference between two groups after exposure to the (375-750) gausses of static magnetic fields and none significance difference between experiments and control groups of fungi after exposures to the short radiation wave and long wave of ultraviolet . Conclusion: No change of dimensional length of fungi after exposure to short UV light, the change which are caused in all types of fungi length after exposure to static magnetic field at range (375-750) gausses